Utilization of Fauna for Therapeutic Purposes by the Newar Community in Bhanu Municipality, Tanahun, Nepal - Shrestha, Nishana; Bajracharya, Sony (Amrit Research Journal, 2023)
The project has interviewed 70 people of Newar community including 37 females and 33 males of different age groups and occupations. Due to major profession of people with farming and animal husbandry, it has provided beneficial knowledge on ethnomedicinal practices to cure different ailment problems like gastritis, asthma, dysentery, cold, cough, back pain, crack heels, anxiety, menstrual cycle problem, burnings, eye cyst etc. 35 species of faunas are used for 9 different ailment categories.  Out of 35 fauna species, 29 were vertebrates (15 Mammals, 11 Aves, 2 Pisces and 1 Reptile) and 6 were invertebrates (Order:  Hymenoptera, Neuroptera, Stylommatophora and Decapoda). Apis sp. (0.1) and Bos taurus (0.9) has the highest Use Value; Gallus gallus domesticus, Bubalus bubalis, Ovis aries, Columba sp. has 100% Fidelity Level. There was no significant correlation between the fidelity level in ailment categories and animal use value (p